2007
DOI: 10.1161/01.str.0000258076.04860.8e
|View full text |Cite
|
Sign up to set email alerts
|

The Factor V Leiden, Prothrombin Gene 20210GA, Methylenetetrahydrofolate Reductase 677CT and Platelet Glycoprotein IIIa 1565TC Mutations in Patients With Acute Ischemic Stroke and Atrial Fibrillation

Abstract: Background and Purpose-We wanted to investigate whether common prothrombotic mutations are more prevalent in patients with atrial fibrillation who have had a stroke than in healthy controls. We also wanted to assess whether early recurrent ischemic cerebrovascular events were more frequent among carriers of the factor V Leiden or the prothrombin gene mutations than among others. Methods-We used a case-control design with 367 patients with acute ischemic stroke and atrial fibrillation (cases) and 482 healthy bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 15 publications
2
19
0
3
Order By: Relevance
“…One third occur in patients younger than 65 years [3]. Etiologies include atrial fibrillation with embolization [3], hypertension, diabetes mellitus, cervicocerebral stenosis [1,2,4], cerebral venous thrombosis [5] and a hypercoaguable state [4,5,6,7,8,9]. …”
Section: Discussionmentioning
confidence: 99%
“…One third occur in patients younger than 65 years [3]. Etiologies include atrial fibrillation with embolization [3], hypertension, diabetes mellitus, cervicocerebral stenosis [1,2,4], cerebral venous thrombosis [5] and a hypercoaguable state [4,5,6,7,8,9]. …”
Section: Discussionmentioning
confidence: 99%
“…4 This mutation is rare in black individuals of African descent. 5 In a relatively large study of prothrombotic gene mutations, Berge et al 6 found a small, nonsignificantly higher risk of early recurrent ischemic cerebrovascular events among patients who were carriers of the Factor V Leiden mutation. Botto et al 7 found increased prevalence of at least one prothrombotic genotype among patients with patent foramen ovale and first-ever ischemic cerebrovascular event before the age of 55 years.…”
Section: Discussionmentioning
confidence: 99%
“…Как уже упоминалось выше, в литературе представ-лены единичные исследования, как отечественные, так и зарубежные, посвященные изучению генетических предикторов возникновения ишемических инсультов у больных с ФП [2][3][4]13]. При этом данные о роли генов тромбофилий в патогенезе тромбоэмболических ослож-нений при ФП остаются противоречивыми.…”
Section: рис 2 отношение шансов частоты генотипов полиморфизма 807сunclassified
“…В литературе представлен ряд исследований, направленных на выявление генетических предикто-ров развития кардиоэмболического инсульта при ФП [2][3][4][5][6][7]. Наиболее изученным генетическим предикто-ром тромбоза является лейденская мутация и поли-морфный маркер 677С<T гена метилентетрагидрофо-латредуктазы (MTHFR) [3].…”
unclassified
See 1 more Smart Citation